Mimesis : the representation of reality in Western literature - Auerbach, Erich, 1892-1957.; Trask, Willard R. (Willard Ropes), 1900-1980. (Princeton ; Oxford : Princeton University Press, 2013)
Shows how from antiquity to the twentieth century literature progressed toward ever more naturalistic and democratic forms of representation. This title offers the optimistic view of European history now appears as a defensive - and impassioned - response to the inhumanity he saw in the Third Reich.
Introduction to the Fiftieth-Anniversary Edition ix 1.Odysseus' Scar 3 2.Fortunata 24 3.The Arrest of Peter Valvomeres 50 4.Sicharius and Chramnesindus 77 5.Roland Against Ganelon 96 6.The Knight Sets Forth 123 7.Adam and Eve 143 8.Farinata and Cavalcante 174 9.Frate Alberto 203 10.Madame Du Chastel 232 11.The World in Pantagruel's Mouth 262 12.L'Humaine Condition 285 13.The Weary Prince 312 14.The Enchanted Dulcinea 334 15.The Faux Devot 359 16.The Interrupted Supper 395 17.Miller the Musician 434 18.In the Hotel de la Mole 454 19.Germinie Lacerteux 493 20.The Brown Stocking 525 Epilogue 554 Appendix 559 Index 575
Includes bibliographical references and index.
ENH
Trim Education
Keywords: Literature -- History and criticism; Reality in literature; Mimesis in literature; English literature